EXPERIMENTAL ASSESSMENT OF A SUSTAINABLE DATA AND POWER TRANSMISSION SYSTEM - Murtadha Shlash; Hassan K. Al-Musawi (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Simultaneous Lightwave Information and Power Transmission (SLIPT) is an emerging technology that combines data and power transfer into an integrated optical link, capable of providing efficient and compact solutions for various clean energy interconnection applications relevant to IoT devices. This work reports an experimental study of an SLIPT system using commercial lasers and photovoltaic (PV) panels for synchronously transmitting information and power. An experimental testbed is performed to analyze SLIPT system prototypes transferring both data and harbored energy over a distance of 12m. The experimental results demonstrate that the Silicon (Si) PV panel can harvest up to 5.5% of laser power with a bit error rate (BER) of 1.32×10-4. This pioneering approach opens up possibilities for low-cost, independent, and self-sustaining systems